Personality masks of mothers of young children: measure development and parenting behavior impact - Li, Ruiqian; Yan, Siyao; Fang, Senwei; Xu, Jiaying; Sun, Chenyu; Shen, Tong (Frontiers in Psychology, 2025)
This study developed and validated an instrument to assess the personality masks of mothers of young children, addressing a gap in the developmental psychology. Using a mixed-methods approach grounded in Carl Jung’s theory of persona, we collected data from 486 mothers in two-parent families in China’s Z region. The research involved three phases: scale development via open-ended questionnaires, which identified a three-dimensional structure of the maternal personality mask (Collective Ideals, Personal Ideals, and Physical/Mental Qualities); confirmatory factor analysis, which validated the model with excellent fit indices; and an implicit memory experiment, which explored the unconscious expression of these dimensions. Results showed significant correlations between the mask dimensions and various parenting behaviors, accounting for notable variance in parenting outcomes. These findings suggest that the personality mask is a valuable construct for understanding maternal behavior, and supporting balanced psychological adaptation in mothers may improve parenting effectiveness. The study provides a practical tool for future research and intervention, while also highlighting the need for further studies with greater cultural diversity and ecological validity.